Integrated transcriptomic and proteomic analyses provide insights into the biosynthesis of Lycii fructus polysaccharides from different cultivation regions - Limei Tong; Yinxiu Jiang; Xinrun Zhang; Xia Zhang; Yihao Zheng; Qiheng Zhao; Sheng Yu; Wenhua Zhang; Gang Ren; Zhanping Chen; Yuling Zhao; Sheng Guo; et al. (Food Chemistry: Molecular Sciences)
Polysaccharides from L. fructus (LFPs) serve as important active biomacromolecules for the wide spectrum of bioactivities exhibited by Lycii fructus. However, the influence of ecological environments on the biosynthesis and structural characteristics of LFPs remains largely unexplored. The present research conducted a comprehensive strategy combining physicochemical structural elucidation, stoichiometric analysis, transcriptomic profiling, and proteomic analysis in L. fructus samples collected from typical cultivation regions including Ningxia, Xinjiang, and Qinghai. The results revealed distinct structural variations in LFPs from Ningxia compared to those from other regions in terms of Glc, Ara, GalA composition percentages as well as overall content. The omics data identified 5531 and 8084 differentially expressed genes (DEGs), as well as 3728 and 4732 differentially expressed proteins (DEPs) in Xinjiang and Qinghai compared to Ningxia, respectively. The integration of transcriptomic and proteomic analyses revealed enrichment of DEGs and DEPs involved in the biosynthesis pathway of LFPs, including UDPs, AXS, and UGDH. Temperature and precipitation were the significant ecological factors affecting LFPs biosynthesis. These comprehensive analyses provide a novel perspective for explaining the important material basis and environmental response mechanism underlying the quality formation of L. fructus.